Comprehensive reform of community health service in east, middle and west regions of China: from patients' perspective. Issue 2 (1st June 2013) - Qin, Jiangmei; Zhang, Yanchun; Zhang, Lifang; Liu, Liqun; Zhou, Wei; Liu, Cailing; Wang, Likun; Li, Jing
Abstract : Objectives: To analyze the satisfaction of patients with community health service (CHS) and the changes of the CHS delivered before and after the new health reform in different regions of China, and to put forward relevant policy recommendations for CHS development. Methods: Twelve community health centers were selected by random sampling in each of the eight typical cities in the east, middle and west regions of China. Questionnaire survey was conducted among patients visiting these institutions during daily work hours. Results: The proportions of the participants who stated that the medical environment, service attitude and medical skills of the doctors were improved were higher in the west region than those of the east and middle regions; but the percentage of patients who held that the drug price had lowered was higher in the east region than those of the middle and west region, the differences were of statistical significance ( P <0.0125). The patients' satisfaction rates with medical environment, service attitude, and technical skills of the medical staff in the west region were 88.9%, 91.5% and 81.6% respectively, which were higher than those in the east and middle regions. In the east region, the satisfaction rate with the reimbursement for this visit was 58.5%, which was highest among the three regions; in the west region, patients' satisfaction rates with drug types and preventive care were 51.5% and 65.9%, respectively, which was significantly higher than those in the east and middle regions ( P <0.0125). As recommended by the participants, the top three aspects of health services that need to be improved were drug type and quality (25.3%), drug prices (21.8%) and technical skills (18.2%) in the east region; infrastructure (28.2%), drug prices (21.8%) and drug types and quality (21.2%) in the middle region; infrastructure (30.8%), drug types and quality (28.1%) and reimbursement (27.9%) in the west region. Conclusions: The comprehensive CHS reform should take the opinions of patients into account; essential drug system should be consolidated continually; and the reform of the payment system should be promoted by actively cooperating with the health insurance organizations.